2007
DOI: 10.1111/j.1365-3059.2007.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of host pH during the wheat–Fusarium culmorum interaction and its influence on the production and activity of pectolytic enzymes

Abstract: The effect on ambient pH of Fusarium culmorum during its growth on mineral medium and in apoplastic fluids from infected wheat seedlings, and the effect on the production and activity of the enzymes pectin lyase (PNL) and polygalacturonase (PG), were investigated. Fungal development on a weakly buffered mineral medium in the pH range 5·0 -8·0, with pectin as the sole carbon source, led to pronounced alkalinization, reaching values above 8·0. The increase in ambient pH was accompanied by enhancement of total PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…Sclerotinia sclerotiorum and Botrytis cinerea both secrete oxalic acid, which has both pH-lowering and elicitor activities during pathogenesis (Kim et al, 2008;Williamson et al, 2007). Although an in planta requirement of an acidic pH for induction of DON production is unknown, the pH optimum of between 2.4 and 3.1 observed here for maximal DON induction is at the extreme end of the previously reported pH of plant apoplastic fluid (Yu et al, 2000), and considerably different from the pH rise from 6 to 7.3 observed in wheat seedlings during crown rot disease caused by Fusarium culmorum (Aleandri et al, 2007). However, accurate measurement of extracellular pH in complex tissues is difficult (Yu et al, 2000), and the pH may not necessarily be homogeneous.…”
Section: Discussioncontrasting
confidence: 40%
“…Sclerotinia sclerotiorum and Botrytis cinerea both secrete oxalic acid, which has both pH-lowering and elicitor activities during pathogenesis (Kim et al, 2008;Williamson et al, 2007). Although an in planta requirement of an acidic pH for induction of DON production is unknown, the pH optimum of between 2.4 and 3.1 observed here for maximal DON induction is at the extreme end of the previously reported pH of plant apoplastic fluid (Yu et al, 2000), and considerably different from the pH rise from 6 to 7.3 observed in wheat seedlings during crown rot disease caused by Fusarium culmorum (Aleandri et al, 2007). However, accurate measurement of extracellular pH in complex tissues is difficult (Yu et al, 2000), and the pH may not necessarily be homogeneous.…”
Section: Discussioncontrasting
confidence: 40%
“…Letters indicate steps supported by gene expression analysis (see Table 2). polygalacturonase by secreting ammonia to increase alkalinisation of the growing media or of the apoplastic fluids of wheat seedlings (Aleandri et al 2007). Merhej et al (2011) have recently shown that Pac1 is a homologue of PacC in F. graminearum.…”
Section: Discussionmentioning
confidence: 99%
“…This change in the pH of the medium is caused by the metabolic activity of the mold. As the mold grows, it utilizes the organic matter present in the culture medium and releases some secondary metabolites as by-products that change the pH of the medium [27]. …”
Section: Methodsmentioning
confidence: 99%